Temperature‐dependent shifts in phenology contribute to the success of exotic species with climate change1. Issue 7 (1st July 2013) - Wolkovich, Elizabeth M.; Davies, T. Jonathan; Schaefer, Hanno; Cleland, Elsa E.; Cook, Benjamin I.; Travers, Steven E.; Willis, Charles G.; Davis, Charles C.
Abstract : Premise of the study: The study of how phenology may contribute to the assembly of plant communities has a long history in ecology. Climate change has brought renewed interest in this area, with many studies examining how phenology may contribute to the success of exotic species. In particular, there is increasing evidence that exotic species occupy unique phenological niches and track climate change more closely than native species. Methods: Here, we use long‐term records of species' first flowering dates from five northern hemisphere temperate sites (Chinnor, UK and in the United States, Concord, Massachusetts; Fargo, North Dakota; Konza Prairie, Kansas; and Washington, D.C.) to examine whether invaders have distinct phenologies. Using a broad phylogenetic framework, we tested for differences between exotic and native species in mean annual flowering time, phenological changes in response to temperature and precipitation, and longer‐term shifts in first flowering dates during recent pronounced climate change ("flowering time shifts"). Key results: Across North American sites, exotic species have shifted flowering with climate change while native species, on average, have not. In the three mesic systems, exotic species exhibited higher tracking of interannual variation in temperature, such that flowering advances more with warming, than native species. Across the two grassland systems, however, exotic species differed from native species primarily in responses to precipitation and soil moisture, not temperature. Conclusions: Our findings provide cross‐site support for the role of phenology and climate change in explaining species' invasions. Further, they support recent evidence that exotic species may be important drivers of extended growing seasons observed with climate change in North America.